Enhanced Adhesion and Dual Antibacterial/Anti-Adherent Function of Polycaprolactone Coatings on Polydopamine-Treated Ti-13ta-12sn Alloy - Hamm-Hahn, L (Elsevier B.V., 2025)
Bioactive polymeric coatings on metallic implants offer significant advantages due to their antimicrobial properties. However, achieving strong and stable adhesion between polymeric coatings and metal surfaces remains challenging, primarily due to differences in surface chemistry. This study explored the surface modification of a Ti-13Ta-12Sn alloy through the in-situ polymerization of 3,4-dihydroxy-L-phenylalanine, leading to the formation of a polydopamine (PDA) layer that enhanced the adhesion of polycaprolactone (PCL) electrospun fiber coatings. Some coatings are also loaded with carvacrol (CAR a natural antimicrobial agent. Adhesion was quantified using a 90° peel test, revealing that PDA pretreatment increased coating adhesion up to three times compared to untreated surfaces. Antibacterial and anti-adherent performance of the PCL and CAR-loaded PCL coatings was evaluated against Staphylococcus aureus (SA), methicillin-resistant S. aureus (MRSA), and Pseudomonas aeruginosa (PA), key pathogens in implant-related infections. A thermodynamic approach was used to estimate the free energy of adhesion (∆Gadh), showing that PCL coatings demonstrated anti-adherent capability toward bacteria, on both treated and untreated Ti-13Ta-12Sn alloy. Biocidal activity tests revealed that CAR-loaded coatings significantly inhibited Gram-positive strains (SA and MRSA) within 3 h, while a 40 % CAR formulation was also effective against PA within 5 h. In conclusion, PDA functionalization significantly improved coating adhesion, and carvacrol conferred dual antibacterial and anti-adherent functionality. This approach represents a promising strategy to enhance the safety and performance of biomedical implants. Its application may be especially beneficial in high-risk devices such as orthopedic and dental prosthetics, where infection prevention and long-term coating stability are essential. © 2025 Elsevier B.V.